Sali Na, Salinas Rosario, Cavite Fisheries Development Center - Magante, Janella Mariz N.; Sarthou, Armin B. (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
Over the past years, the Philippines has experienced several threats to food security. The widening income gap between the upper and lower classes makes food security elusive to the poor. Filipinos from the lower income brackets have less access to healthy and nutritious food. The food security of the country relies mostly on the agriculture sector. As the country is susceptible to natural calamities, this poses a threat to food availability. This project entitled "Sali Na, Salinas : Rosario Fisheries Development Center" aims to address the issue of food insecurity through the development of an integrated waterfront complex which promotes sustainable fisheries and aquaculture. Focusing on proper fish handling promotes efficient practices to reduce post-production losses. Focusing on aquaculture provides local employment and additional fish supply to meet increasing demand. Focusing on livelihood boosts the tinapa industry of the town and increases community participation. Fish handling aquaculture, and livelihood facilities shall allow the project to be an efficient fisheries development center.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Aquatic resources; Aquatic facilities